[Four DLSU faculty were included in the 1997 Canon of Philippine Literature ] - Medina, Buenaventura S., Jr. (Animo Repository, 1998)
Four La Salle faculty were included in the 1997 Canon of Philippine Literature. The Canon was a result of a survey conducted among teachers, critics, scholars, writers, publishers, and officials of the Dept. of Education, Culture, and Sports and the Commission on Higher Education.